Change in soil chemical attributes and yield of a common-bean crop in response to steel slag application - da Silva, Alessandra Vieira [UNESP]; Deus, Angélica Cristina Fernandes [UNESP]; de Souza, Mara Lúcia Cruz [UNESP]; Broetto, Fernando [UNESP]; Büll, Leonardo Theodoro [UNESP] (Southern Cross Publishing, 2023)
Most agricultural soils in Brazil are classified as acid, which limits agricultural production in the country, warranting the application of acidity correctives. The present study examined the effect of steel slag application on chemical characteristics of the soil as well as on the metabolic responses and yield of common-bean plants in a no-till system. The experiment was laid out in a randomized-block design with 42-m2 subplots in a 7×2 factorial arrangement, with four replicates. Treatments consisted of two factors, namely, acidity correctives and application forms. The following correctives were tested: steel slag (T1), wollastonite (T2), ladle furnace slag (T3), stainless steel slag (T4), calcined agricultural limestone (T5), agricultural limestone (T6), and a control without correctives (C). The application forms were surface application and incorporation (20 cm). Ten months after the last reapplication of the acidity correctives, a soil probe sampler was used to collect samples from the 0–10 cm, 10–20 cm, and 20–40 cm layers for chemical analysis. The common-bean crop was established after 16 months of the applications, and the following parameters were evaluated 40 days after germination: plant height; leaf dry weight; relative water content; electrolyte losses; pigment content (Clo a, Clo b, and carotenoids); leaf macronutrient and micronutrient content; total soluble protein content; leaf silicon content; enzyme activities of superoxide dismutase, peroxidase, and catalase; and gas exchange. At the end of the crop cycle, grain production and yield components were evaluated. Phosphorus, pH, base saturation, and Si increased with the application of silicates, influencing the number of plants m-1 and 100-grain weight; however, grain yield did not change.
Keywords: carbonate; silicates; silicon